Development and Evaluation of Novel Metformin Derivative Metformin Threonate for Brain Ischemia Treatment - Zhang, Gufang; Chen, Shuangshuang; Jia, Jia; Liu, Chun; Wang, Weipeng; Zhang, Hongjian; Zhen, Xuechu (Frontiers in Pharmacology, 2022)
Epidemiologic data reveal that diabetes patients taking metformin exhibit lower incidence of stroke and better functional outcomes during post-stroke neurologic recovery. We previously demonstrated that chronic post-ischemic administration of metformin improved the functional recovery in experimental cerebral ischemia. However, few beneficial effects of metformin on acute phase of cerebral ischemia were reported either in experimental animals or in stroke patients which limits the application of metformin in stroke. We hypothesized that slow cellular uptake of metformin hydrochloride may contribute to the lack of efficacy in acute stroke. We recently developed and patented a novel metformin derivative, metformin threonate (SHY-01). Pharmacokinetic profile in vivo and in cultured cells revealed that metformin is more rapidly uptake and accumulated from SHY-01 than that of metformin hydrochloride. Accordingly, SHY-01 treatment exhibited more potent and rapid activation of AMPK. Furthermore, SHY-01 elicited a stronger inhibition on microglia activation and more potent neuroprotection when compared to metformin hydrochloride. SHY-01 administration also had superior beneficial effects on neurologic functional recovery in experimental stroke, and offered a strong protection against acute cerebral ischemia with reduced infarct volume and mortality, as well as the improved sensorimotor and cognitive functions in rats. Collectively, these results indicated that SHY-01, had improved pharmacokinetic and pharmacological profile, produced more potent protective effects on acute stroke and long-term neurological damage. We propose that SHY-01 is a very promising therapeutic candidate for cerebral ischemic stroke.